Q:-solve this and then find pq
![{a}^{4} + {b}^{4} = ( {a}^{2} + pab + {b}^{2} )( {a}^{2} - qab + {b}^{2} ) {a}^{4} + {b}^{4} = ( {a}^{2} + pab + {b}^{2} )( {a}^{2} - qab + {b}^{2} )](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B4%7D+%2B+%7Bb%7D%5E%7B4%7D+%3D+%28+%7Ba%7D%5E%7B2%7D+%2B+pab+%2B+%7Bb%7D%5E%7B2%7D+%29%28+%7Ba%7D%5E%7B2%7D+-+qab+%2B+%7Bb%7D%5E%7B2%7D+%29)
solve this easy Question
Answers
Step-by-step explanation:
Q:-solve this and then find pq
_ _ _ _ _ _ _ _ _ _ _ _ _ _ _✍️
══════════XXX═════════════
On comparing both sides :-
we get p=2 & q =2
══════════XXX═════════════
HOPE IT HELPS YOU..
_____________________
Thankyou:)
Step-by-step explanation:
f(x) = kx³ – 8x² + 5
Roots are α – β , α & α +β
Sum of roots = – (-8)/k
Sum of roots = α – β + α + α +β = 3α
= 3α = 8/k
= k = 8/3α
or we can solve as below
f(x) = (x – (α – β)(x – α)(x – (α +β))
= (x – α)(x² – x(α+β + α – β) + (α² – β²))
= (x – α)(x² – 2xα + (α² – β²))
= x³ – 2x²α + x(α² – β²) – αx² +2α²x – α³ + αβ²
= x³ – 3αx² + x(3α² – β²) + αβ² – α³
= kx³ – 3αkx² + xk(3α² – β²) + k(αβ² – α³)
comparing with
kx³ – 8x² + 5
k(3α² – β²) = 0 => 3α² = β²
k(αβ² – α³) = 5
=k(3α³ – α³) = 5
= k2α³ = 5
3αk = 8 => k = 8/3α
(8/3α)2α³ = 5
=> α² = 15/16
=> α = √15 / 4